1974
DOI: 10.1159/000260100
|View full text |Cite
|
Sign up to set email alerts
|

Natural Elements of the Periodic Table in Human Dental Enamel

Abstract: Analysis was carried out for 66 minor inorganic elements of whole enamel samples obtained from 28 bicuspid teeth ( < 20 years). After each sample was analysed separately by the spark source mass spectroscopy technique, it was found that 35 elements were present in enamel in detectable and quantitatable concentrations but that 31 elements, if present, were below the detectable limits of the technique. Minor elements occurring in the greatest concentration ( > 10 μg/g dry wt) were F, Mg, S, Cl, K, Zn and Sr. Oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1

Year Published

1974
1974
2008
2008

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(23 citation statements)
references
References 3 publications
1
21
1
Order By: Relevance
“…The high concentrations of cadmium found in the teeth of the animals in the present experiment were unexpected and are the highest ever reported for enamel tissue (10,11). In swine consuming 1350 ppm Cd in the diet, whole incisors contained 212 ppm Cd (11).…”
Section: Discussioncontrasting
confidence: 44%
“…The high concentrations of cadmium found in the teeth of the animals in the present experiment were unexpected and are the highest ever reported for enamel tissue (10,11). In swine consuming 1350 ppm Cd in the diet, whole incisors contained 212 ppm Cd (11).…”
Section: Discussioncontrasting
confidence: 44%
“…Previous trial sam ples and analyses had shown no contamination oc curred from the instruments used. Further details of the sample preparation were given by Losee et al [1974b]. The prepared samples were thorough ly cleansed with distilled deionized water and sent for analysis by spark source mass spectrometry us ing an AEI Model MS 702R (Accu-labs Research Inc., Wheat Ridge, Colo.).…”
Section: Methodsmentioning
confidence: 99%
“…It is generally accepted that Al is a normal constituent of first and adult teeth (457,458) which fluctuates in the various anatomical portions of the tooth with age (459,460). Discolored areas of sound teeth have been observed to contain markedly elevated concentrations of both Al and F. Human dental calculus has also been shown to contain high concentrations of Al (461) which have been shown to inhibit alkaline phosphatase (462) and alkaline phosphomonoesterase (463) from human dental plaque.…”
Section: August 1974mentioning
confidence: 99%